PENGARUH KOMPETENSI, DISIPLIN DAN MOTIVASI TERHADAP KINERJA PEJABAT FUNGSIONAL PADA KEMENTERIAN LINGKUNGAN HIDUP DAN KEHUTANAN DI PROPINSI SUMATERA SELATAN - Lalu Suaidi Basri; Sri Rahayu; Choiriyah Choiriyah (KOLEGIAL, 2020)
The Office of Religious Affairs (KUA) is one part of the structure and spearhead of the Ministry of Religion in religious service and guidance in the community. As a technical unit dealing directly with the community, the performance of KUA employees will be a concern. The Factors can affect the performance among leadership, motivation and work discipline. This research aims to determine the effect of leadership, motivation and work discipline on the performance of KUA employees in Musi Banyuasin Regency. This research is a quantitative study with causal descriptive analysis techniques, classic assumption tests, multiple linear regression analysis and coefficient tests. Data were collected using a questionnaire with 114 respondents. Based on the results of data processing with the coefficient of determination or Ajusted R Square 0.422, shows that employee performance is influenced by leadership, motivation and work discipline by 42.2%, while the rest is influenced by other variables outside this study. the F test results obtained Fcount > Ftable (28.520 > 3.08), with a significance level of 0.000 < 0.05, this shows that leadership, motivation and work discipline together have a significant and positive effect on employee performance. Partially, leadership and work discipline have a significant effect on employee performance, while motivation does not significantly influence the performance of KUA employees in Musi Banyuasin Regency. In addition to the factors of good leadership and high work discipline, the Ministry of Religion in particular the head of the KUA needs to pay attention to matters that can increase the motivation of KUA employees in order to improve their performance in the future.